Comprehensive analysis of lysine lactylation in Frankliniella occidentalis - An, Dong; Song, Liyun; Li, Ying; Shen, Lili; Miao, Pu; Wang, Yujie; Liu, Dongyang; Jiang, Lianqiang; Wang, Fenglong; Yang, Jinguang (Frontiers in Genetics, 2022)
Western flower thrips (Frankliniella occidentalis) are among the most important pests globally that transmit destructive plant viruses and infest multiple commercial crops. Lysine lactylation (Klac) is a recently discovered novel post-translational modification (PTM). We used liquid chromatography-mass spectrometry to identify the global lactylated proteome of F. occidentalis, and further enriched the identified lactylated proteins using Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO). In the present study, we identified 1,458 Klac sites in 469 proteins from F. occidentalis. Bioinformatics analysis showed that Klac was widely distributed in F. occidentalis proteins, and these Klac modified proteins participated in multiple biological processes. GO and KEGG enrichment analysis revealed that Klac proteins were significantly enriched in multiple cellular compartments and metabolic pathways, such as the ribosome and carbon metabolism pathways. Two Klac proteins were found to be involved in the regulation of the TSWV transmission in F. occidentalis. This study provides a systematic report and a rich dataset of lactylation in F. occidentalis proteome for potential studies on the Klac protein of this notorious pest.